A method for high-throughput acquisition of hardness of FCC CoCrNi alloy
Patent Information
- Application Number
- CN202310960877.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-08-02
AI Technical Summary
但当时更多关注的是一维扩散成分梯度,二维扩散区域成分关注不够,且设计的组合合金所包含的二维扩散区域成分有限,没有充分发挥该方法的优势
[0046] 1) Aiming at the problem that multi-component alloys have a vast composition space and how to efficiently obtain corresponding hardness, the present invention provides a high-throughput research method, which mainly includes preparation of diffusion multiple joints and nanoindentation characterization. Through observing that the shape of the FCC phase region in the isothermal section phase diagram of the Co-Cr-Ni ternary system is approximately trapezoidal, the method designs a "grid-shaped" diffusion multiple joint experimental scheme, and the four alloy compositions constituting the diffusion multiple joint are respectively the four vertex compositions of the trapezoid. Such design enables that after diffusion is completed, the intermediate two-dimensional diffusion region of the "grid-shaped" diffusion multiple joint can cover the composition interval of the entire FCC phase, significantly reducing the number of alloys to be prepared and lowering the research and development cost. In addition, the idea of the present method can also be extended to other alloy systems and other single-phase regions, and diffusion multiple joints such as "pin-shaped" and "grid-shaped" can be designed according to the shape of the composition interval range on the phase diagram.
Smart Images

Figure CN116973259B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metallic materials technology, and in particular to a high-throughput method for obtaining the hardness of FCC CoCrNi alloy. Background Technology
[0002] With the increasing demand for high-performance materials, in addition to traditional alloys based on one or two elements, novel multi-principal-element high-entropy / medium-entropy alloys have attracted widespread attention. Numerous studies have shown that they exhibit excellent performance in many fields, including high hardness, high strength, good thermal stability, and corrosion resistance, demonstrating significant application potential. The multi-principal-element characteristics of high-entropy / medium-entropy alloys greatly enhance the freedom of alloy composition selection and performance control, and their composition is not limited to equiproportional or near-equiproportional mixing. From the perspective of thermodynamic phase diagrams, current research on metallic materials covers the entire composition range, significantly increasing the difficulty of exploring alloy property laws and composition design. Clearly, the traditional "trial and error" method is time-consuming and requires substantial human and material resources. Therefore, efficiently designing alloy compositions to obtain high-performance alloys is of paramount importance.
[0003] Multiscale simulation technology for materials is an important tool for the design of new materials and the development of new processes. In order to ensure the reliability of simulation results, a large amount of experimental data is needed to support them, and high-throughput experimental schemes are undoubtedly a good choice.
[0004] In early 2000, Zhao Jicheng and others developed the "diffusion multi-junction" method to rapidly determine phase diagrams and diffusion kinetics data, and to test the micro-region properties of materials based on compositional gradients. However, at that time, more attention was paid to the one-dimensional diffusion compositional gradient, while insufficient attention was paid to the composition of the two-dimensional diffusion region. Furthermore, the two-dimensional diffusion region composition contained in the designed composite alloys was limited, and the advantages of this method were not fully utilized.
[0005] Therefore, there is an urgent need for an efficient method to obtain the correspondence between alloy composition and hardness. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a high-throughput method for obtaining the hardness of FCCCoCrNi alloys. Specifically, this method combines diffusion multi-junction technology with nanoindentation to obtain the hardness of FCCCoCrNi alloys. Taking a Co-Cr-Ni ternary alloy as an example, this invention selects four alloy components based on its 1200℃ isothermal phase diagram, ensuring that the connection of these four component points on the phase diagram covers the entire FCC phase region. Combined with the automated nanoindentation testing features, a large amount of composition-performance relationship data can be rapidly obtained, serving multi-scale simulation processes for material and process design, significantly reducing R&D costs and shortening the cycle time.
[0007] The objective of this invention can be achieved through the following technical solutions:
[0008] A method for obtaining the hardness of FCC CoCrNi alloy in high throughput includes the following steps:
[0009] Step 1: The purity of the raw materials Co, Cr and Ni is ≥99.95wt.%. They are prepared according to the weight ratio based on the design requirements to obtain a well-proportioned Co, Cr and Ni.
[0010] Step 2: Melt the Co, Cr, and Ni proportioned in Step 1 to prepare pure Co ingots, pure Ni ingots, and Co... 1-a Cr a Alloy ingots and Ni 1-b Cr b Alloy ingots, where 0.3≤a≤0.4 and 0.4≤b≤0.5, are four types of smelted ingots. High-purity argon is used as the protective gas throughout the entire process.
[0011] Step 3: Place the four types of smelted ingots from Step 2 into a sealed device filled with argon gas for homogenization heat treatment and quench them before removing them to obtain four types of button ingots after homogenization heat treatment.
[0012] Step 4: Cut the four types of homogenized heat-treated button ingots from Step 3 into metal blocks, and perform a first metallographic treatment on them to obtain flat, smooth, and clean sample surfaces, yielding pure Co, pure Ni, and Co alloy after metallographic treatment. 1-a Cr a and Ni 1-b Cr b ;
[0013] Step 5: Using a Mo fixture, transfer the pure Co, pure Ni, and alloy Co from the metallographic treatment in Step 4. 1-a Cr a and Ni 1-b Cr b Two well-secured one-dimensional diffusion couples, Co-Ni and Co, were obtained by stacking and fastening. 1-a Cr a -Ni 1-b Cr b ;
[0014] Step Six: Place the one-dimensional diffusion couple secured in Step Five into a sealed device filled with argon gas, then perform a first annealing treatment and quench it before removing it to complete the bonding, obtaining two bonded one-dimensional diffusion couples, Co-Ni and Co. 1-a Cr a -Ni 1- b Cr b ;
[0015] Step 7: Subject the two bonded one-dimensional diffusion couples Co-Ni and Co obtained in Step 6 1-a Cr a -Ni 1-b Cr b to a second metallographic treatment again, and fasten them with a Mo fixture to prepare a diffusion multiple, so as to obtain the prepared diffusion multiple;
[0016] Step 8: Place the diffusion multiple sample prepared in Step 7 in a sealing device filled with argon, and then perform a second annealing treatment to enable diffusion;
[0017] Step 9: After diffusion is completed, subject the diffusion multiple sample to a third metallographic treatment, then observe the morphology by electron probe and test the composition of the intermediate two-dimensional diffusion region;
[0018] Step 10: Based on the morphology observed by the electron probe and the composition test positions, use nanoindentation to measure the hardness of the alloy at corresponding positions.
[0019] Further, after Step 10, perform Step 11: draw a relationship diagram according to the alloy composition and hardness tested by the electron probe and nanoindentation.
[0020] Further, the diffusion multiple may be a "tian"-shaped diffusion multiple or a "pin"-shaped diffusion multiple.
[0021] Preferably, the diffusion multiple is a "tian"-shaped diffusion multiple.
[0022] Further, in Step 1, the design requirement is based on the compositions of four endpoints of the FCC phase region on the 1200°C isothermal section phase diagram of the Co-Cr-Ni ternary system.
[0023] Further, the four endpoint compositions can almost cover the entire FCC phase region.
[0024] Preferably, the four endpoint compositions are pure Co, pure Ni and alloy Co 1-a Cr a and Ni 1-b Cr b .
[0025] More preferably, a=0.3 and b=0.4.
[0026] Preferably, smelting is performed in a non-consumable vacuum arc furnace, and the sample is repeatedly turned over 5 times during smelting.
[0027] Further, in Step 3, homogenization heat treatment is performed at 1200°C with a holding time of 240h.
[0028] Further, in Step 3, the sealing device is a sealed tube.
[0029] Further, in step 4, the first metallographic treatment comprises sequentially grinding with 400#, 800#, 1200#, 1500# and 2000# sandpapers, followed by polishing with Al2O3 polishing slurry.
[0030] Further, in step 4, the button ingots after four homogenization heat treatments in step 3 are respectively cut into 4×4×4 mm 3 metal blocks.
[0031] Further, in step 6, the first annealing treatment is performed at 1200°C with heat preservation for 24 h.
[0032] Further, in step 6, the sealing device is a sealed glass tube.
[0033] Further, in step 7, the second metallographic treatment comprises sequentially grinding with 400#, 800#, 1200#, 1500# and 2000# sandpapers, followed by polishing with Al2O3 polishing slurry.
[0034] Further, in step 7, the connection surfaces of the two one-dimensional diffusion couples for preparing the "grid-shaped" diffusion multiple node shall be aligned, the Co end is connected with Co 1-a Cr a end is attached, and the Ni end is connected with Ni 1-b Cr b end is attached.
[0035] Further, in step 8, the second annealing treatment is performed at 1200°C with heat preservation for 72 h.
[0036] Further, in step 8, the sealing device is a sealed glass tube.
[0037] Further, in step 9, the third metallographic treatment comprises sequentially grinding with 400#, 800#, 1200#, 1500# and 2000# sandpapers, followed by polishing with Al2O3 polishing slurry.
[0038] Further, in step 9, the intermediate two-dimensional diffusion region is a square region with a transverse length of 480 μm and a longitudinal length of 900 μm, which takes the sample center as the geometric center.
[0039] Preferably, the transverse length is the union of effective diffusion intervals in the two upper and lower parallel directions, and the longitudinal length is the union of effective diffusion intervals in the two left and right parallel directions.
[0040] Preferably, the effective diffusion interval is determined by line scanning at positions 1 mm in four directions of up, down, left and right from the sample center by an electron probe, and observing the interval with composition gradient.
[0041] Preferably, the 1 mm line scanning is performed to avoid the influence of two-dimensional diffusion.
[0042] Preferably, the line scanning direction is perpendicular to the joint surface of the one-dimensional diffusion couple, and the line scanning length is 1 mm, ensuring that the effective one-dimensional diffusion interval can be covered.
[0043] Further, in step nine, the electron probe test is performed by uniformly arranging a 15×15 matrix for point testing in the entire two-dimensional diffusion region.
[0044] Further, in step ten, the nanoindentation measurement is performed in a continuous stiffness loading mode at room temperature, with a maximum indentation depth of 1000 nm and a strain rate of 0.2 s -1 , and a thermal drift of 0.05 nm / s.
[0045] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0046] 1) Aiming at the problem that multi-component alloys have a vast composition space and how to efficiently obtain corresponding hardness, the present invention provides a high-throughput research method, which mainly includes preparation of diffusion multiple joints and nanoindentation characterization. Through observing that the shape of the FCC phase region in the isothermal section phase diagram of the Co-Cr-Ni ternary system is approximately trapezoidal, the method designs a "grid-shaped" diffusion multiple joint experimental scheme, and the four alloy compositions constituting the diffusion multiple joint are respectively the four vertex compositions of the trapezoid. Such design enables that after diffusion is completed, the intermediate two-dimensional diffusion region of the "grid-shaped" diffusion multiple joint can cover the composition interval of the entire FCC phase, significantly reducing the number of alloys to be prepared and lowering the research and development cost. In addition, the idea of the present method can also be extended to other alloy systems and other single-phase regions, and diffusion multiple joints such as "pin-shaped" and "grid-shaped" can be designed according to the shape of the composition interval range on the phase diagram.
[0047] 2) The diffusion multiple joint sample prepared by the present invention is directly used for subsequent composition testing and performance characterization after metallographic treatment, so as to efficiently screen out compositions meeting performance requirements, greatly shortening the research and development cycle of new material compositions. Meanwhile, a large amount of composition and performance data obtained by the present invention can also be used for diffusion research and analysis of alloy solid solution strengthening mechanism, providing a theoretical basis for alloy design.
[0048] 3) The high-throughput method for obtaining hardness of FCC CoCrNi alloy according to the present invention combines the diffusion multiple joint sample preparation technology with characterization means such as electron probe and nanoindentation, efficiently obtains alloy hardness within a wide composition range, and the result shows that the overall alloy hardness increases along the CoCr composition boundary. Description of Drawings
[0049] Figure 1 is the 1200°C isothermal section phase diagram of the Co-Cr-Ni ternary system of the present invention and the four selected composition points;
[0050] Figure 2 This is a flowchart illustrating the high-throughput process for obtaining the hardness of FCC CoCrNi alloy according to the present invention.
[0051] Figure 3 This is the backscattering image of the diffusion multi-unit sample of the present invention after nanoindentation testing;
[0052] Figure 4 This is a graph showing the relationship between the hardness of the nanoindentation test and the alloy composition according to the present invention. Detailed Implementation
[0053] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.
[0054] Obviously, the embodiments described below are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art of metallic materials based on the embodiments of the present invention without inventive effort are within the protection scope of the present invention.
[0055] Any preparation methods, materials, structures, or composition ratios not explicitly described in this technical solution are considered common technical features disclosed in the prior art.
[0056] A method for obtaining the hardness of FCC CoCrNi alloy in high throughput includes the following steps:
[0057] Step 1: The purity of the raw materials used, namely elemental Co, Cr and Ni, is ≥99.95wt.%, and they are prepared according to the weight ratio based on design requirements;
[0058] Step 2: Melt the proportioned Co, Cr, and Ni to prepare pure Co, pure Ni, and Co. 1-a Cr a Alloy ingots and Ni 1-b Cr b Alloy ingots, where 0.3≤a≤0.4, 0.4≤b≤0.5, are produced using high-purity argon as a protective gas throughout the entire process;
[0059] Step 3: The smelted ingot is placed in a sealed tube filled with argon gas for homogenization heat treatment and then quenched before being removed.
[0060] Step 4: Cut the homogenized heat-treated button ingots into 4×4×4mm pieces. 3a metal block, which is subjected to metallographic treatment to obtain a flat, smooth and clean sample surface;
[0061] Step 5: Pure Co, pure Ni, alloy Co after metallographic treatment are clamped with a Mo fixture 1-a Cr a and Ni 1-b Cr b are fastened in a stacking manner;
[0062] Step 6: Place the fastened one-dimensional diffusion couple in a sealed glass tube filled with argon, then perform annealing treatment and quench to take out to complete bonding;
[0063] Step 7: Bond the two bonded one-dimensional diffusion couples Co-Ni and Co 1-a Cr a -Ni 1-b Cr b is subjected to metallographic treatment again, and a "field"-shaped diffusion multiple is prepared by fastening with a Mo fixture;
[0064] Step 8: Place the prepared "field"-shaped diffusion multiple sample in a sealed glass tube filled with argon, then perform annealing treatment to allow diffusion;
[0065] Step 9: After diffusion is completed, subject the "field"-shaped diffusion multiple sample to metallographic treatment, then observe the morphology by electron probe microanalysis and test the composition of the intermediate two-dimensional diffusion region;
[0066] Step 10: Based on the morphology and composition test positions observed by the electron probe microanalysis, nanoindentation is used to measure the hardness of the alloy at the corresponding positions.
[0067] The present invention provides a high-throughput method for obtaining the hardness of FCC CoCrNi alloys by combining diffusion multiple technology and nanoindentation, comprising: designing and preparing pure metals Co, Ni and binary alloy Co for "field"-shaped diffusion multiple according to the phase diagram 1-a Cr a , Ni 1-b Cr b ; subjecting the pure metal raw materials weighed according to the proportion to vacuum smelting; then sealing the smelted button ingot in a glass tube filled with argon for homogenization treatment; subjecting the treated sample to wire cutting and metallographic treatment; and using a Mo fixture to hold the polished pure metals Co, Ni and alloy Co 1-a Cr a and Ni 1-b Cr bThe blocks are fastened by stacking; then placed in a sealed glass tube, and kept at 1200°C for 24h to complete the bonding; the two bonded one-dimensional diffusion couples are subjected to metallographic treatment again and fastened by a Mo fixture, and kept at 1200°C for 72h to prepare a "field"-shaped diffusion multiple junction; after diffusion, the composition of the two-dimensional diffusion region in the middle of the "field"-shaped diffusion multiple junction sample is tested by an electron probe; finally, the hardness of the two-dimensional diffusion region is tested by a nanoindenter. The "field"-shaped diffusion multiple junction sample prepared by the present invention almost covers the composition of the entire FCC phase region in the Co-Cr-Ni system, and through subsequent automatic nanoindentation testing, the corresponding relationship between alloy composition and hardness can be efficiently obtained, which greatly shortens the research and development cycle for exploring new material compositions, solid solution strengthening mechanisms and alloy diffusion behaviors, and saves manpower and material resources.
[0068] Figure 1 In the description, FCC is a face-centered cubic unit cell, and BCC is a body-centered cubic unit cell.
[0069] Example
[0070] The specific implementation steps for high-throughput obtaining the hardness of FCC CoCrNi alloy in this example include:
[0071] 1) As shown in Figure 1 , select four endpoint components of the FCC phase region on the 1200°C isothermal section phase diagram of the Co-Cr-Ni ternary system as the alloy composition for preparing the "field"-shaped diffusion multiple junction sample. The purity of the raw material elemental Co, Cr and Ni used is ≥99.95wt.%, and the ingredients are prepared according to the weight ratio based on the above four endpoint components;
[0072] 2) Place the proportioned Co, Cr and Ni in a non-consumable vacuum arc furnace for smelting to obtain pure Co, pure Ni and Co 0.7 Cr0 .3 and Ni 0.6 Cr 0.4 alloy ingots. Before smelting, evacuate until the vacuum degree reaches 9.99×10 -4 Pa, then fill with high-purity argon, repeat this process three times, and turn the sample over repeatedly for 5 times during the smelting process to promote uniform mixing of each element;
[0073] 3) Place the smelted ingot in a sealed tube filled with argon for homogenization heat preservation at 1200°C for 240h, then quench rapidly in ice water to make the element distribution more uniform, and promote grain growth to reduce the influence of grain boundaries on diffusion;
[0074] 4) Cut the button ingot after homogenization heat treatment into 4×4×4mm 3a metal block, which is subjected to metallographic treatment, that is, polished with 400#, 800#, 1200#, 1500# and 2000# sandpapers and then polished with Al2O3 polishing slurry to obtain a flat, smooth and clean sample surface;
[0075] 5) Pure Co, pure Ni and alloy Co after metallographic treatment are clamped with a Mo fixture 0.7 Cr 0.3 and Ni 0.6 Cr 0.4 are fastened in a stacking manner, as shown in Figure 2 ;
[0076] 6) The fastened one-dimensional diffusion couple is placed in a sealed glass tube filled with argon, then annealed at 1200°C for 24 hours, and quickly quenched in ice water, so that the one-dimensional diffusion couple is well connected;
[0077] 7) The two diffused one-dimensional diffusion couples Co-Ni and Co 0.7 Cr 0.3 -Ni 0.6 Cr 0.4 are subjected to metallographic treatment again, and fastened by a Mo fixture to prepare a "field"-shaped diffusion multiple node, as shown in Figure 2 ;
[0078] 8) The prepared "field"-shaped diffusion multiple node sample is placed in a sealed glass tube filled with argon, then annealed at 1200°C for 72 hours to complete diffusion and bonding;
[0079] 9) The bonded "field"-shaped diffusion multiple node sample is subjected to metallographic treatment, then the morphology is observed by electron probe and the composition of the intermediate two-dimensional diffusion region is tested. The operation of testing the composition of the intermediate two-dimensional diffusion region by electron probe includes: firstly, performing line scanning at positions 1mm in four directions of up, down, left and right from the center of the "field"-shaped diffusion multiple node sample to avoid the influence of two-dimensional diffusion; the line scanning length is 1mm and is perpendicular to the one-dimensional diffusion bonding surface, so that it can effectively cover the one-dimensional diffusion interval; the effective one-dimensional diffusion intervals in four directions of up, down, left and right can be obtained according to the line scanning results, and the union of the effective intervals in two parallel directions of up-down and left-right is selected as the side length of the rectangle; this rectangular space covers the two-dimensional diffusion region, and then an electron probe device is used to uniformly set a 15×15 matrix in this rectangular space for point testing;
[0080] 10) Based on the morphology observed by the electron probe and the composition test positions, nanoindentation is used to measure the hardness of the alloy at the corresponding positions, as shown in Figure 3 , the nanoindentation test is performed at room temperature in a continuous stiffness loading mode, with a maximum indentation depth of 1000nm and a strain rate of 0.2s -1 , and a thermal drift of 0.05nm / s;
[0081] 11) Based on the alloy composition and hardness obtained from electron probe microanalysis and nanoindentation testing, plot a relationship diagram, such as... Figure 4 As shown.
[0082] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A method for high-throughput acquisition of the hardness of FCC CoCrNi alloy, characterized in that, Comprising the following steps: Step 1: The purity of the raw materials elemental Co, Cr and Ni used is ≥ 99.95 wt.%, and burdening is carried out by weight ratio according to design requirements, to obtain proportioned Co, Cr and Ni; Step 2: Melt the Co, Cr, and Ni proportioned in Step 1 to prepare pure Co ingots, pure Ni ingots, and Co... 1- a Cr a Alloy ingots and Ni 1-b Cr b Alloy ingots, where 0.3≤a≤0.4 and 0.4≤b≤0.5, are four types of smelted ingots. High-purity argon is used as the protective gas throughout the entire process. Step 3: Placing the four smelted ingots obtained in step 2 respectively in a sealed device filled with argon for homogenization heat treatment, taking them out after quenching, to obtain four button ingots after homogenization heat treatment; Step 4: Cut the four types of homogenized heat-treated button ingots from Step 3 into metal blocks, and perform a first metallographic treatment on them to obtain pure Co, pure Ni, and Co alloy after metallographic treatment. 1-a Cr a and Ni 1-b Cr b ; Step 5: Using a Mo fixture, transfer the pure Co, pure Ni, and alloy Co from the metallographic treatment in Step 4. 1-a Cr a and Ni 1-b Cr b Two well-secured one-dimensional diffusion couples, Co-Ni and Co, were obtained by stacking and fastening. 1-a Cr a -Ni 1-b Cr b ; Step Six: Place the one-dimensional diffusion couple secured in Step Five into a sealed device filled with argon gas, then perform a first annealing treatment and quench it before removing it to complete the bonding, obtaining two bonded one-dimensional diffusion couples, Co-Ni and Co. 1-a Cr a -Ni 1-b Cr b ; Step 7: Combine the two one-dimensional diffusion couples Co-Ni and Co from Step 6. 1-a Cr a -Ni 1-b Cr b A second metallographic treatment was performed, and diffusion multi-component nodes were prepared by fastening them with Mo fixtures to obtain the prepared diffusion multi-component nodes. Step 8: Placing the diffusion multiple sample prepared in step 7 in a sealed device filled with argon, then performing a second annealing treatment to allow diffusion; Step 9: After diffusion is completed, subjecting the diffusion multiple sample to a third metallographic treatment, then observing the morphology through an electron probe and testing the composition of the intermediate two-dimensional diffusion region; Step 10: Based on the morphology observed by the electron probe and the composition test positions, measuring the hardness of the alloy at corresponding positions by nanoindentation; In step 1, the design requirements are based on the four endpoint compositions of the FCC phase region on the 1200 °C isothermal section phase diagram of the Co-Cr-Ni ternary system; by observing that the shape of the FCC phase region in the isothermal section phase diagram of the Co-Cr-Ni ternary system is approximately trapezoidal, a "field-shaped" diffusion multiple experimental scheme is designed, and the four alloy compositions constituting the diffusion multiple are respectively the four vertex compositions of the trapezoid; In step seven, the two one-dimensional diffusion coupler faces of the prepared diffusion multi-component node are aligned, with the Co end aligned with the Co end. 1-a Cr a The Ni end is bonded to the Ni end, while the Ni end is bonded to the Ni end. 1-b Cr b End fitting.
2. The method for obtaining the hardness of FCC CoCrNi alloy in high throughput according to claim 1, characterized in that, The four endpoints are composed of pure Co, Ni, and alloy Co. 1-a Cr a and Ni 1-b Cr b .
3. The method for obtaining the hardness of FCC CoCrNi alloy in high throughput according to claim 1, characterized in that, In step 2, the smelting is carried out in a non-consumable vacuum arc furnace, and the sample is turned over repeatedly for 5 times during smelting; and / or In step 3, the homogenization heat treatment is carried out at 1200 °C with heat preservation for 240 h; and / or In step 4, the first metallographic treatment comprises sequentially grinding with 400#, 800#, 1200#, 1500# and 2000# sandpaper and then polishing with Al2O3 polishing liquid; and / or In step 6, the first annealing treatment is carried out at 1200 °C with heat preservation for 24 h; and / or In step 7, the second metallographic treatment comprises sequentially grinding with 400#, 800#, 1200#, 1500# and 2000# sandpaper and then polishing with Al2O3 polishing liquid; and / or In step 8, the second annealing treatment is carried out at 1200 °C with heat preservation for 72 h; and / or In step 9, the third metallographic treatment comprises sequentially grinding with 400#, 800#, 1200#, 1500# and 2000# sandpaper and then polishing with Al2O3 polishing liquid.
4. The method for obtaining the hardness of FCC CoCrNi alloy in high throughput according to claim 1, characterized in that, In step 9, the intermediate two-dimensional diffusion region is a square region with the sample center as the geometric center, a transverse length of 480 μm and a longitudinal length of 900 μm.
5. The method for obtaining the hardness of FCC CoCrNi alloy in high throughput according to claim 4, characterized in that, The transverse length is the union of effective diffusion intervals in two upper and lower parallel directions, and the longitudinal length is the union of effective diffusion intervals in two left and right parallel directions.
6. The method for obtaining the hardness of FCC CoCrNi alloy in high throughput according to claim 5, characterized in that, The effective diffusion interval is determined by performing line scanning via the electron probe at a position 1 mm away from the sample center in four directions: up, down, left and right, and observing the interval with composition gradient.
7. The method for obtaining the hardness of FCC CoCrNi alloy in high throughput according to claim 6, characterized in that, The line scanning at the position 1 mm away from the center is to avoid the influence of two-dimensional diffusion.
8. The method for obtaining the hardness of FCC CoCrNi alloy in high throughput according to claim 6, characterized in that, The line scanning direction is perpendicular to the bonding surface of the one-dimensional diffusion couple, and the line scanning length is 1 mm.
9. The method for obtaining the hardness of FCC CoCrNi alloy in high throughput according to claim 1, characterized in that, In step nine, the electron probe testing involves uniformly setting a 15×15 matrix across the entire two-dimensional diffusion region for point testing; and / or In step ten, the nanoindentation measurement is performed at room temperature using a continuous stiffness loading mode, with a maximum indentation depth of 1000 nm and a strain rate of 0.2 s⁻¹. -1 Thermal drift is 0.05 nm / s.
Citation Information
Patent Citations
Design method of multi-component high-strength titanium alloy
CN108446478A